Rating Systems and the End-Game Effect: When Reputation Works and when It Doesn't - Chiara Belletti; Elizaveta Pronkina; Michelangelo Rossi (CESifo GmbH, 2024)
Do rating systems provide incentives to sellers when they are about to exit a market? Using data from Airbnb, this paper examines how end-of-game considerations affect hosts' effort decisions. We take advantage of a regulation on short-term rentals in the City of Los Angeles to identify hosts who anticipated their imminent exit from the platform due to non-compliance with new eligibility rules. We focus on hosts who left the platform as a result of the regulation and measure their effort with listing's ratings in effort-related categories such as check-in, communication and cleanliness. With a Difference-in-Differences and Event Study approach, we compare how listing's effort-related ratings changed, compared to ratings on location, after the regulation announcement and during its implementation. We document a statistically significant decrease in effort in the last periods of the hosts' career. Our findings provide insights for platform managers, highlighting the adverse effects of end-of-game considerations on how rating systems affect sellers' incentives for the provision of high-quality services.
Keywords: D82; L14; L86; 330; rating systems; online reputation; digital platforms